The right to health in Chile. Preliminary notes from the public health perspective - Foitzick Zumelzu, Macarena; Gattini Collao, Cesar; Westermeyer Hernández, Felipe (Revista de Derecho Público, 2024)
This paper begins a new research about the right to health definition, which included different fields of studies, especially law, philosophy and public health. This paper reviews the right to health as a social right and the difficulties in determine his meaning for legal and public health sciences, and how these two fields develop the concept of right to health.